PEMBERIAN KOMPRES DINGIN PADA NY. A DENGAN KETIDAKNYAMANAN NYERI LUKA PERINEUM DI PKD TLAHAB LOR - Barkah Ruliyanto Ruliyanto; Eko Sari Ajiningtyas; Dwi Astuti (Jurnal Ilmiah Medsains, 2023)
The incidence of perineal injuries from WHO (World Health Organization) data in mothers giving birth in the world there are 2.7 million cases, where this figure is expected to reach 6.3 million in 2050. The results of a preliminary study conducted on October 28, 2022, at the Health Center Karangreja obtained data from 234 mothers giving birth, and from January to September 2022, it was found that 47 of them came from the village of Tlahab Lor. Cold compresses, or cold therapy, are a physical therapy modality that uses the physical properties of cold to treat various conditions, including perineal wound pain. To determine the effectiveness of giving cold compresses to postpartum mothers with perineal wound discomfort. This study used a case study method with respondents giving birth to perineal wounds on day 2. Using three instruments, namely observation sheets, interview sheets, and the Gordon assessment format, This research was conducted in Tlahab Lor Village for 3 days, from April 30 to May 2, 2023. After 3 days of action, the perineal wound pain was reduced. The pain scale before the cold compress was 6, but after being given a cold compress, it was 2. Applying cold compresses to mothers with perineal wounds is effective in reducing pain and discomfort.